Análise evolutiva de aeronaves da aviação geral - Pinheiro, Felipe [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
The aircraft fleet in Brazil and the United States, the two countries with the largest fleets in the world, is predominantly composed of General Aviation aircraft such as single and twin-engine piston and turboprop aircraft. The economic impact that these aircraft generate and the growth of the world fleet are expressive. This work analyzes general aviation aircraft conceived between the 1970s and 2010 and makes parametric and comparative studies in order to study the performance parameters and identify trends. Using the aircraft flight handbooks, it was possible to extract data and make estimates for the desired performance parameters. These results pointed to trends of increased cruise speed, increased fuel consumption and decreased distance due to consumption for single-engine piston aircraft and decreased cruise speed, decreased fuel consumption and increased distance due to consumption of twin-engine piston aircraft , single-engine and twin-engine turboprop.

A frota de aviões no Brasil e nos Estados Unidos, os dois países com as maiores frotas do mundo, é predominantemente composta por aeronaves da aviação geral como monomotores e bimotores à pistão e turboélice. O impacto econômico que estas aeronaves geram e o crescimento da frota mundial são expressivos. O presente trabalho analisa aeronaves da aviação geral concebidas entre as décadas de 1970 e 2010 e faz estudos paramétricos e comparativos afim de estudar os parâmetros de performance e identificar tendências. Fazendo uso dos manuais de voo das aeronaves, foi possível extrair dados e realizar estimativas para os parâmetros de desempenho desejados. Esses resultados apontaram tendências de aumento de velocidade de cruzeiro, aumento de consumo de combustível e diminuição da distância por consumo para as aeronaves monomotoras pistão e diminuição da velocidade de cruzeiro, diminuição de consumo de combustível e aumento da distância por consumo das aeronaves bimotoras à pistão, monomotoras e bimotoras turboélice.
Evolutionary analysis of general aviation aircrafts
Keywords: Aeronaves; Desempenho; Aviação